The effects of mangrove stem extract compared to mangrove leaf extract in inhibiting Streptococcus mutans and Candida albicans growth on acrylic plate: Perbandingan pengaruh ekstrak batang mangrove dengan ekstrak daun mangrove dalam menghambat pertumbuhan Streptococcus mutans dan Candida albicans pada plat akrilik - Andi Adytha Mutiah Itte Rusiaty; Moh. Dharma Utama; Muh. Ikbal; Eri H. Jubhari (Makassar Dental Journal PDGI Makassar, 2019)
Objective: This study aimed to determine the effects of mangrove (Avicennia marina) stem extract compared to the leaf extract in inhibiting the growth of S. mutans and C. albicans on acrylic plate. Methods: Mangrove stems and leaves extract was made with concentrations of 5%, 10%, 20% and cleaning agents as the control. The acrylic plates were soaked in the mangrove extracts for 10 minutes. The calculation of the number of bacterial and fungal colonies were performed afterward, then the data were analyzed by one way Anova and post hoc test (Tukey HSD). Results: The number of colonies of mangrove stems extract were calculated for C. albicans with concentrations of 5% = 558.6, 10% = 264.8, 20% = 212.2, and control = 4.4, whereas the S.mutans with concentrations of 5% = 161.4, 10% = 54.6, 20% = 37.2, and the control = 131. Statistical analysis of mangrove leaves extract with concentrations of 5%= 7.185, 10% = 8.360, 20% = 8.485, and the control 9.105 showed the different significant zones of inhibition of S.mutans based on the control. The 5% of concentrations of mangrove leaves extract showed the inhibition activities against S.mutans but did not show the inhibition zone against C.albicans, while the 5% concentrations of mangrove stem extract showed the inhibition activities against S.mutans and C.albicans. Conclusions: Mangrove stems extracts were more effective than the leaves extracts in inhibiting the growth of S. mutans and C. albicans on acrylic plate. The mangrove extracts, both the stems and leaves extracts, had higher effectiveness in inhibiting S. mutans compared to C. albicans activities. Keywords: acrylic plate, Candida albicans, mangrove leaf extract (Avicennia marina), mangrove stem extract, Streptococcus mutans